Photo-thermal response type composite antibacterial wound dressing as well as preparation method and application thereof
By using core-shell structural composite materials in antibacterial wound dressings, the coordinated release of silver nanorods and antibacterial drugs has been solved in the existing technology with high cost, toxic side effects and fixed release time, and a safe and effective antibacterial effect has been achieved.
Patent Information
- Application Number
- CN202411456543.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
The existing photothermal-responsive antibacterial wound dressings have high cost, complex preparation process, easy enrichment of nanosilver in the body, resulting in toxic side effects, and the release time of a single antibacterial agent is fixed, so it is impossible to take into account both short-acting and long-acting antibacterials.
Using core-shell structure composite materials, silver nanorods as cores and mesoporous silica as shells, doped with antibacterial drugs, nanofiber membranes are prepared by electrospinning, and the synergistic release of silver ions and drugs is activated by near-infrared light to reduce nanometers Silver usage and cytotoxicity.
The preparation process is simplified, the cost is reduced, and the safe release of nano silver is achieved, taking into account both short-acting and long-acting antibacterial effects, improving the antibacterial ability and safety of the dressing.
Smart Images

Figure CN119280451A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antibacterial dressings, and in particular to a photothermal responsive composite antibacterial wound dressing and a preparation method and application thereof. Background Art
[0002] The skin is the largest organ in the human body and the first immune barrier to protect the human body. Under normal physiological conditions, human skin has the ability to repair itself. However, if trauma, burns, scalds or wounds left after surgery caused by major accidents are not treated in time or are treated improperly, it will cause problems such as wound ulceration and long healing time. In severe cases, it will cause major disability or even death of the patient, which poses a great threat to human health.
[0003] In current clinical applications, traditional wound dressings (such as gauze, bandages, and cotton pads) have become the most commonly used type of dressings due to their advantages of simple preparation, wide availability, and low price. However, such dressings only act as a physical barrier and have no promoting effect on the wound healing process. Secondly, the mesh of materials such as gauze is large, and foreign matter such as floating bacteria and dust in the air can easily invade the wound and cause infection. At the same time, new granulation tissue can easily grow into the mesh of the gauze, causing adhesion between the wound and the dressing, which can easily cause secondary trauma and pain and discomfort to the patient when changing the dressing.
[0004] Nanofiber materials, due to their special microstructure, can effectively promote cell adhesion and proliferation. Therefore, they have gradually become an excellent choice for wound dressing matrix materials in recent years. In particular, continuous nanofiber membranes prepared by electrospinning technology have shown broad application prospects in wound dressings due to their controllable microstructure, large specific surface area, high porosity, excellent mechanical properties, and ability to simulate extracellular matrix structure. Therefore, using nanofiber membranes prepared by electrospinning to load some pro-repair growth factors or antibacterial agents and achieve their controlled release is an effective means to accelerate wound repair and skin regeneration.
[0005] Recently, in order to reduce secondary damage to wounds during dressing changes, people have gradually increased their research on self-peeling wound dressings, but there are some shortcomings. Chinese patent CN110983483B discloses a parallel composite fiber composed of hydrophilic antibacterial fiber and hydrophobic photothermal conversion fiber, but the photosensitizer and antibacterial agent of this fiber are two separate components, and the preparation process is complicated. Chinese patent CN118044521A discloses a method for preparing spherical zinc-silver materials, but this method does not involve the control of silver ion release and may cause strong toxic side effects. Chinese patent CN115920119A discloses a photothermal oxygen-carrying hydrogel wound dressing, but the preparation method of the dressing is cumbersome, the process is complex, and the cost is high.
[0006] In summary, the currently developed photothermal responsive antibacterial wound dressings have relatively high costs and complex preparation processes. The antibacterial properties of nanosilver are closely related to their shape. Only silver nanorods (AgNR) with a specific aspect ratio will exhibit photothermal responsive antibacterial properties. At the same time, nanosilver particles have the disadvantages of being easily enriched in the body and producing strong toxic side effects, having a single function when used for surface modification of bone implants, and having poor biological activity and being prone to rejection reactions. Wound dressings adhere to new tissues during wound recovery, which may cause secondary damage when changing dressings. The release time of a single antibacterial agent is fixed, and it cannot take into account both short-term and long-term antibacterial effects. Therefore, it is necessary to develop a composite antibacterial wound dressing to promote the practical application of composite antibacterial wound dressings in clinical practice. Summary of the invention
[0007] In view of the shortcomings existing in the above-mentioned background technology, the present invention mainly targets the following shortcomings: wound dressings are easy to adhere to wounds, causing secondary damage; nanosilver particles are easy to be enriched in the body and produce strong toxic side effects; the addition of photosensitizers and antibacterial agents in photothermal responsive wound dressings increases the complexity of the process and increases the cost; the release time of a single antibacterial agent is fixed, and short-term and long-term antibacterial effects cannot be taken into account. The present invention provides a photothermal responsive composite antibacterial wound dressing, a preparation method and an application. The wound dressing has a nanosilver antibacterial agent with a core-shell structure, which greatly alleviates the cytotoxicity of nanosilver and the problem of secondary damage when changing the wound dressing. The wound dressing uses a core-shell structure composite material to act as a photosensitizer and an antibacterial agent at the same time, simplifies the preparation steps of the photothermal responsive composite wound dressing, and reduces the cost. And the wound dressing can give play to the release characteristics of the drug and nanosilver, taking into account short-term antibacterial effects and long-term antibacterial effects. The dual-factor synergistic antibacterial of nanosilver and antibacterial drugs can reduce the amount of nanosilver used, thereby reducing cytotoxicity.
[0008] The first object of the present invention is to provide a photothermal responsive composite antibacterial wound dressing, wherein the wound dressing comprises a nanofiber membrane capable of generating a photothermal response to near-infrared light; The nanofiber membrane is a spinning product obtained by electrostatic spinning using a spinning solution prepared with polyvinyl alcohol, polyacrylic acid and a core-shell structure composite material; The core-shell structure composite material is a composite material with a core-shell structure formed by silver nanorods as cores and mesoporous silica as shells; Wherein, the mesoporous silica shell of the core-shell structure composite material is doped with antibacterial drugs.
[0009] Preferably, the mass ratio of the polyvinyl alcohol to the polyacrylic acid is 1:1-4, and the core-shell structure composite material accounts for 1%-30% of the mass of the fiber membrane.
[0010] Preferably, the molar ratio of the silver nanorods to the mesoporous silica is 1:3-7; the length of the silver nanorods is 60-150 nm, and the aspect ratio is 3-5:1; the thickness of the mesoporous silica shell is 10-80 nm; Wherein, the silver nanorods are wrapped with gold bipyramid seeds.
[0011] Preferably, the core-shell structure composite material is prepared according to the following steps: The silver nanorods are dispersed in a chloroform solution, and then added to a CTAB aqueous solution to obtain a homogeneous oil-in-water microemulsion; the chloroform in the obtained microemulsion is evaporated to obtain an AgNR@CTAB solution; The AgNR@CTAB solution and the tetraethyl orthosilicate solution are added into the alkaline aqueous solution containing CTAB. After the reaction is completed, a core-shell structure composite material is obtained. The core-shell structure composite material is soaked in the drug solution for a period of time and then separated to obtain the core-shell structure composite material with the antibacterial drug doped in the mesoporous silica shell.
[0012] Preferably, the antibacterial drug includes ciprofloxacin, vancomycin or daqingmycin; the doping amount of the antibacterial drug accounts for 5% to 30% of the mass of the core-shell structure composite material.
[0013] Preferably, the core-shell structure composite material can accelerate the release of silver ions and drugs after being irradiated with near-infrared light; and the wound dressing can perform photothermal conversion for near-infrared light with a wavelength of 780 to 850 nm.
[0014] Preferably, during the electrospinning process, the diameter of the spun nanofibers is 200-1000 nm.
[0015] The second object of the present invention is to provide a method for preparing a photothermal responsive composite antibacterial wound dressing, comprising: The polyvinyl alcohol and polyacrylic acid are uniformly mixed in the DCM solution to obtain a transparent solution; After the core-shell structure composite material is uniformly dispersed in the DMF solution, it is added into the transparent solution and stirred for 5 to 8 hours to obtain a spinning solution; The nanofiber membrane is prepared by electrospinning the spinning solution.
[0016] Preferably, the electrospinning process parameters are set as follows: voltage 18-20 kV, syringe propulsion speed 0.8-1.2 mL / h, distance between syringe needle and roller collector 13-16 cm; The spinning environment temperature was 25±2°C and the relative humidity was 45±2%.
[0017] The third object of the present invention is to provide a photothermal responsive composite antibacterial wound dressing for use in the preparation of wound treatment drugs.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a photothermal responsive composite antibacterial wound dressing, a preparation method and an application thereof, wherein the wound dressing comprises a nanofiber membrane capable of generating a photothermal response to near-infrared light; the nanofiber membrane is a spinning product obtained by electrostatic spinning of a spinning solution prepared with polyvinyl alcohol, polyacrylic acid and a core-shell structure composite material; the core-shell structure composite material is a composite material of a core-shell structure formed with silver nanorods as cores and mesoporous silica as shells; wherein the mesoporous silica shell of the core-shell structure composite material is doped with antibacterial drugs. The mutual cross-linking of polyvinyl alcohol and polyacrylic acid can improve the physical properties of the fiber membrane and provide certain mechanical properties required for wound dressings. The core-shell composite material is distributed in the fiber membrane of the cross-linked network structure, which can inhibit the release of silver ions and antibacterial drugs therein.
[0019] The present invention obtains an antibacterial fiber membrane with a photothermal response effect, and alleviates the cytotoxicity of a core-shell structure composite material doped with antibacterial drugs through photothermal assistance.
[0020] The invention has simple process and simple equipment, and both the photosensitizer and the antibacterial agent are borne by the core-shell structure composite material, which simplifies the production process and is convenient for industrial production.
[0021] The invention adopts a gold seed method to prepare silver nanorods, and prepares a silver nanorod composite material wrapped by ion-doped mesoporous silica by a sol-gel method. CTAB is used as a template agent and TEOS is used as a silicon source to form a core-shell structure. The silver nanorods with a core-shell structure can slowly release silver ions through mesoporous channels, thereby avoiding toxic side effects caused by the sudden release of silver ions.
[0022] The core-shell structure composite material obtained by the present invention can release the drug in the mesoporous silica in a short period of time to achieve short-term antibacterial effect, and then near-infrared light is irradiated as needed to promote the release of silver ions to achieve long-term antibacterial effect.
[0023] The present invention can adjust the release of silver ions of the dressing as needed by adjusting the power and frequency of near-infrared light irradiation, thereby improving the antibacterial ability of the dressing. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the fiber membrane provided in Example 1.
[0025] Figure 2 This is the silver ion release curve of the fiber membrane provided in Example 1 under near-infrared light irradiation.
[0026] Figure 3These are pictures and infrared photographs of the self-curling process of the fiber membrane provided in Example 1 under near-infrared light irradiation over time.
[0027] Figure 4 Qualitative antibacterial performance test of the fiber membrane provided in Examples 1 to 3.
[0028] Figure 5 This is a cytotoxicity test of the fiber membranes provided in Examples 1 to 3.
[0029] Figure 6 This is the cell morphology after co-culturing the fiber membranes and cells provided in Examples 1 to 3. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0031] In view of the problems existing in the current photothermal responsive wound dressings, the present invention provides a self-stripping wound dressing with photothermal response which has simple operation, stable process and strong applicability.
[0032] A first aspect of the present invention provides a photothermal responsive composite antibacterial wound dressing, the wound dressing comprising a nanofiber membrane capable of generating a photothermal response to near-infrared light; The nanofiber membrane is a spinning product obtained by electrostatic spinning using a spinning solution prepared with polyvinyl alcohol, polyacrylic acid and a core-shell structure composite material; The core-shell structure composite material is a composite material with a core-shell structure formed by silver nanorods as cores and mesoporous silica as shells; Wherein, the mesoporous silica shell of the core-shell structure composite material is doped with antibacterial drugs.
[0033] The mass ratio of the polyvinyl alcohol to the polyacrylic acid is 1:1-4, and the core-shell structure composite material accounts for 1%-30% of the mass of the fiber membrane.
[0034] The molar ratio of the silver nanorods to the mesoporous silica is 1:3-7; the length of the silver nanorods is 60-150 nm, and the aspect ratio is 3-5:1; the thickness of the mesoporous silica shell is 10-80 nm; Wherein, the silver nanorods are wrapped with gold bipyramid seeds.
[0035] Specifically, the core-shell structure composite material is prepared according to the following steps: The silver nanorods are dispersed in a chloroform solution, and then added to a CTAB aqueous solution to obtain a homogeneous oil-in-water microemulsion; the chloroform in the obtained microemulsion is evaporated to obtain an AgNR@CTAB solution; The AgNR@CTAB solution and the tetraethyl orthosilicate solution were added to the alkaline aqueous solution containing CTAB. After the reaction was completed, a core-shell structure composite material (AgNR@MSN) was obtained. The core-shell structure composite material is soaked in the drug solution for a period of time and then separated to obtain the core-shell structure composite material with the antibacterial drug doped in the mesoporous silica shell.
[0036] According to the present invention, the antibacterial drugs include antibiotics such as ciprofloxacin, vancomycin, and daqingmycin. In the embodiments, ciprofloxacin is taken as an example.
[0037] The doping amount of the antibacterial drug accounts for 5% to 30% of the mass of the core-shell structure composite material.
[0038] The core-shell structure composite material can accelerate the release of silver ions and drugs after being irradiated with near-infrared light; the wound dressing can perform photothermal conversion on near-infrared light with a wavelength of 780 to 850 nm.
[0039] During the electrospinning process, the diameter of the spun nanofibers is 200~1000nm.
[0040] In one embodiment, the specific preparation method of the silver nanorods wrapped with gold bipyramids is as follows: 1.1) At room temperature, CTAC (50 mM, 8.95 mL), citric acid (5 mM, 1 mL) and HAuCl4 (50 mM, 0.05 mL) were added to the solution in sequence, and sodium borohydride (25 mM, 0.25 mL) was used to quickly reduce HAuCl4 to prepare gold seeds. After 2 minutes, the bottle cap was closed and the seed solution was heated at 80°C for 90 minutes with gentle stirring to obtain a gold seed solution. Finally, the seed solution was stored at room temperature. The gold seed solution was used to grow small gold bipyramids.
[0041] 1.2) An aliquot of the gold seed solution (1 mL) was added to a growth aqueous solution containing CTAB (20 mL, 100 mM), HAuCl4 (0.2 mL, 50 mM), AgNO3 (0.2 mL, 10 mM), HCl (0.4 mL, 1M), and ascorbic acid (AA) (0.16 mL, 100 mM) under vigorous stirring. The mixture was allowed to stand at 30 °C for 4 h to obtain gold bipyramids. After 4 h of reaction, the solution was centrifuged (10000 rpm, 30 min) to remove excess reagents and redispersed in CTAC (10 mM, 1 mL).
[0042] 1.3) Under vigorous stirring, the solution of AgNO3 (10 mM) and AA (100 mM) was added to the gold bipyramid (10 mL) solution containing CTAC (10 mM) at room temperature. During the entire addition process, the molar ratio [AA]: [Ag + ] = 4 remained constant. After the addition was completed, the mixture was vigorously stirred at 60 °C for 2 h. Finally, the resulting solution was centrifuged (10000 rpm, 30 min) and redispersed in water to obtain silver nanorods.
[0043] Among them, the length and aspect ratio of the bipyramid can be changed by changing the concentration ratio of silver nitrate and gold to meet different needs.
[0044] In one embodiment, the specific preparation method of the core-shell structure composite material with antibacterial drugs doped in the mesoporous silica shell is as follows: 2.1) The prepared silver nanorods were dispersed in a chloroform (CHCl3) solution to prepare 3.0 mL (5 mg / mL) of a mixed solution. The mixed solution was added to a 10 mL aqueous solution containing 0.2 g of CTAB and stirred vigorously to obtain a homogeneous water-in-oil type microemulsion. The obtained microemulsion was heated at 65°C for 20 min to evaporate CHCl3 to obtain an AgNR@CTAB solution.
[0045] 2.2) Dissolve 0.05 g of CTAB in 86 mL of water under stirring at room temperature, add NaOH (0.7 mL, 2 M), then add the AgNR@CTAB solution obtained in step 2, and heat the mixture to 60°C. While stirring vigorously, add 0.75 mL of TEOS to the reaction solution. After the addition is complete, react for 2 h. After the reaction is completed, centrifuge at 10,000 rpm for 5 min to collect the product.
[0046] 2.3) The template was removed by extraction with an ethanol solution containing ammonium nitrate (6 g / L) and refluxed for 24 h to obtain the sample, which was then washed and dried and labeled as AgNR@MSN.
[0047] 2.4) AgNR@MSN was soaked in 10 mg / mL ciprofloxacin solution for 12 h with constant stirring. The particles obtained by centrifugation were freeze-dried to obtain a core-shell structure composite material doped with drugs, which was labeled as AgNR@MSN-CI.
[0048] The second aspect of the present invention provides a method for preparing a photothermal responsive composite antibacterial wound dressing, comprising: Polyvinyl alcohol (PVA) and polyacrylic acid (PAA) were uniformly mixed in DCM solution to obtain a transparent solution; After the core-shell structure composite material is uniformly dispersed in the DMF solution, it is added into the transparent solution and stirred for 5 to 8 hours to obtain a spinning solution; The nanofiber membrane is prepared by electrospinning the spinning solution.
[0049] The electrospinning process parameters are set as follows: voltage 18-20 kV, syringe propulsion speed 0.8-1.2 mL / h, and the distance between the syringe needle and the roller collector is 13-16 cm; preferably, voltage 18 kV, propulsion speed 1 mL / h, and the distance between the syringe needle and the roller collector is 15 cm; The spinning environment temperature was 25±2°C and the relative humidity was 45±2%.
[0050] In one embodiment, a method for preparing a photothermal responsive composite antibacterial wound dressing is provided, and the specific preparation method is as follows: 3.1) At room temperature, weigh 2 g of PVA / PAA powder (PVA:PAA=3:7 (wt%)) and dissolve it in 12 mL of DCM solution. Stir it magnetically until the solution is transparent. At the same time, add 0.1 g of the core-shell composite material powder doped with antibacterial drugs to 8 mL of DMF solution and stir it to disperse it evenly. After both solutions are evenly dispersed, mix them and continue stirring for 6 hours to prepare a blended electrospinning solution.
[0051] 3.2) Inject the prepared electrospinning solution into two 5 mL syringes, install the syringes correctly and connect the lines, then turn on the equipment. The specific electrospinning process parameters are set as follows: voltage 18 kV, propulsion speed 1 mL / h, and the distance between the syringe needle and the roller collector is 15 cm. The spinning environment temperature is 25 ± 2℃ and the relative humidity is 45 ± 2%.
[0052] The invention can improve the physical properties of the fiber membrane by cross-linking polyvinyl alcohol and polyacrylic acid, and provide certain mechanical properties required for wound dressing. The core-shell composite material is distributed in the fiber membrane with a cross-linked network structure, and can inhibit the release of silver ions and antibacterial drugs therein.
[0053] Among them, the amount of antibacterial agent carried on the fiber can be changed to meet different needs by changing the incorporation mass of the core-shell structure composite material doped with antibacterial drugs.
[0054] A third aspect of the present invention provides an application of a photothermal responsive composite antibacterial wound dressing in the preparation of a wound treatment drug.
[0055] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0056] Example 1 A method for preparing a photothermal responsive composite antibacterial wound dressing comprises the following steps: Step 1: Prepare silver nanorods by the gold seed method described above; Step 2: The prepared silver nanorods were dispersed in a chloroform (CHCl3) solution to prepare 3.0 mL (5 mg / mL) of a mixed solution. The mixed solution was added to 10 mL of an aqueous solution containing 0.2 g of CTAB and stirred vigorously to obtain a homogeneous water-in-oil microemulsion. The obtained microemulsion was heated at 65 °C for 20 min to evaporate CHCl3 to obtain an AgNR@CTAB solution.
[0057] Step 3: Dissolve 0.05 g of CTAB in 86 mL of water with stirring at room temperature, add NaOH (0.7 mL, 2 M), then add the AgNR@CTAB solution obtained in step 2, and heat the mixture to 60°C. While stirring vigorously, add 0.75 mL of TEOS to the reaction solution. After the addition is complete, react for 2 h. After the reaction is completed, centrifuge at 10,000 rpm for 5 min to collect the product, which is AgNR@MSN without removing the template CTAB.
[0058] Step 4: Extract with ethanol solution containing ammonium nitrate (6 g / L) and reflux for 24 h to remove the template. After obtaining the sample, wash and dry it, and the sample is labeled as AgNR@MSN. This step is mainly to remove the CTAB template in step 3, so that the MSN shell forms channels.
[0059] AgNR@MSN was immersed in 10 mg / mL ciprofloxacin solution for 12 h with constant stirring. The particles obtained by centrifugation were freeze-dried to obtain a core-shell structure composite material doped with drugs, which was labeled as AgNR@MSN-CI.
[0060] Step 5: At room temperature, weigh 2 g of PVA / PAA powder (PVA:PAA=3:7) and dissolve it in 12 mL of DCM solution. Stir it magnetically until the solution is transparent. At the same time, add 0.02 g of AgNR@MSN-CI powder to 8 mL of DMF solution and stir it to disperse it evenly. After both solutions are evenly dispersed, mix them and continue stirring for 6 hours to prepare a blended electrospinning solution.
[0061] Step 6: Inject the prepared electrospinning solution into two 5 mL syringes, install the syringes correctly and connect the lines, then turn on the equipment. The specific electrospinning process parameters are set as follows: voltage 18 kV, propulsion speed 1 mL / h, and the distance between the syringe needle and the roller collector is 15 cm. The spinning environment temperature is 25 ± 2℃, and the relative humidity is 45 ± 2%. The collected electrospun fiber membrane is treated at 125℃ for 1.5h to crosslink it, and the obtained fiber membrane is labeled as 1%AgNR@MSN-CI / PVA / PAA.
[0062] Example 2 A method for preparing a photothermal responsive composite antibacterial wound dressing comprises the following steps: Step 1: Prepare silver nanorods by the gold seed method described above; Step 2: The prepared silver nanorods were dispersed in a chloroform (CHCl3) solution to prepare 3.0 mL (5 mg / mL) of a mixed solution. The mixed solution was added to 10 mL of an aqueous solution containing 0.2 g of CTAB and stirred vigorously to obtain a homogeneous water-in-oil microemulsion. The obtained microemulsion was heated at 65 °C for 20 min to evaporate CHCl3 to obtain an AgNR@CTAB solution.
[0063] Step 3: Dissolve 0.05 g of CTAB in 86 mL of water with stirring at room temperature, add NaOH (0.7 mL, 2 M), then add the AgNR@CTAB solution obtained in step 2, and heat the mixture to 60°C. While stirring vigorously, add 0.75 mL of TEOS to the reaction solution. After the addition is complete, react for 2 h. After the reaction is completed, centrifuge at 10,000 rpm for 5 min to collect the product.
[0064] Step 4: The template was removed by extraction with an ethanol solution containing ammonium nitrate (6 g / L) and refluxed for 24 h. After obtaining the sample, it was washed and dried, and the sample was labeled as AgNR@MSN.
[0065] AgNR@MSN was immersed in 10 mg / mL ciprofloxacin solution for 12 h with constant stirring. The particles obtained by centrifugation were freeze-dried to obtain a core-shell structure composite material doped with drugs, which was labeled as AgNR@MSN-CI.
[0066] Step 5: At room temperature, weigh 2 g of PVA / PAA powder (PVA:PAA=3:7) and dissolve it in 12 mL of DCM solution. Stir it magnetically until the solution is transparent. At the same time, add 0.1 g of AgNR@MSN-CI powder to 8 mL of DMF solution and stir it to disperse it evenly. After both solutions are evenly dispersed, mix them and continue stirring for 6 hours to prepare a blended electrospinning solution.
[0067] Step 6: Inject the prepared electrospinning solution into two 5 mL syringes, install the syringes correctly and connect the lines, then turn on the equipment. The specific electrospinning process parameters are set as follows: voltage 18 kV, propulsion speed 1 mL / h, and the distance between the syringe needle and the roller collector is 15 cm. The spinning environment temperature is 25 ± 2℃, and the relative humidity is 45 ± 2%. The collected electrospun fiber membrane is treated at 125℃ for 1.5h to crosslink it, and the obtained fiber membrane is labeled as 5%AgNR@MSN-CI / PVA / PAA.
[0068] The only difference between Example 2 and Example 1 is the input amount of AgNR@MSN-CI during electrospinning.
[0069] Example 3 A method for preparing a photothermal responsive composite antibacterial wound dressing comprises the following steps: Step 1: Prepare silver nanorods by the gold seed method described above; Step 2: The prepared silver nanorods were dispersed in a chloroform (CHCl3) solution to prepare 3.0 mL (5 mg / mL) of a mixed solution. The mixed solution was added to 10 mL of an aqueous solution containing 0.2 g of CTAB and stirred vigorously to obtain a homogeneous water-in-oil microemulsion. The obtained microemulsion was heated at 65 °C for 20 min to evaporate CHCl3 to obtain an AgNR@CTAB solution.
[0070] Step 3: Dissolve 0.05 g of CTAB in 86 mL of water with stirring at room temperature, add NaOH (0.7 mL, 2 M), then add the AgNR@CTAB solution obtained in step 2, and heat the mixture to 60°C. While stirring vigorously, add 0.75 mL of TEOS to the reaction solution. After the addition is complete, react for 2 h. After the reaction is completed, centrifuge at 10,000 rpm for 5 min to collect the product.
[0071] Step 4: The template was removed by extraction with an ethanol solution containing ammonium nitrate (6 g / L) and refluxed for 24 h. After obtaining the sample, it was washed and dried, and the sample was labeled as AgNR@MSN.
[0072] AgNR@MSN was immersed in 10 mg / mL ciprofloxacin solution for 12 h with constant stirring. The particles obtained by centrifugation were freeze-dried to obtain a core-shell structure composite material doped with drugs, which was labeled as AgNR@MSN-CI.
[0073] Step 5: At room temperature, weigh 2 g of PVA / PAA powder (PVA:PAA=3:7) and dissolve it in 12 mL of DCM solution. Stir it magnetically until the solution is transparent. At the same time, add 0.2 g of AgNR@MSN-CI powder to 8 mL of DMF solution and stir it to disperse it evenly. After both solutions are evenly dispersed, mix them and continue stirring for 6 hours to prepare a blended electrospinning solution.
[0074] Step 6: Inject the prepared electrospinning solution into two 5 mL syringes, install the syringes correctly and connect the lines, then turn on the equipment. The specific electrospinning process parameters are set as follows: voltage 18 kV, propulsion speed 1 mL / h, and the distance between the syringe needle and the roller collector is 15 cm. The spinning environment temperature is 25 ± 2℃, and the relative humidity is 45 ± 2%. The collected electrospun fiber membrane is treated at 125℃ for 1.5h to crosslink it, and the obtained fiber membrane is labeled as 10%AgNR@MSN-CI / PVA / PAA.
[0075] The only difference between Example 3 and Example 1 is the input amount of AgNR@MSN-CI during electrospinning.
[0076] To illustrate the relevant properties of the composite material provided by the present invention, see Figures 1 to 6 As shown, the following is explained.
[0077] Figure 1 This is a scanning electron microscope image of the AgNR@MSN-CI / PVA / PAA fiber membrane described in Example 1 of the present invention. Figure 1 It can be seen that the core-shell structured AgNR@MSN-CI is evenly dispersed in the PVA / PAA fiber, and the fiber membrane successfully carries the photothermal responsive core-shell structure composite material. The present invention realizes the preparation of the electrospinning fiber membrane carrying the photothermal responsive core-shell structure composite material.
[0078] In subsequent experiments, the irradiation power and irradiation time of NIR light were 1 W / cm² and 3 min.
[0079] Figure 2 This is the silver ion release curve of the electrospun fiber membrane under near-infrared light irradiation and a partial enlarged diagram (see the right figure) described in Example 1 of the present invention. Figure 2It can be seen that after near-infrared light irradiation, the amount of silver ions released from the fiber membrane increases significantly. The present invention realizes the photothermal response of silver ion controlled release.
[0080] Figure 3 The following are pictures and thermal images of the fiber membrane described in Example 1 of the present invention curling up over time under near-infrared light irradiation. Figure 3 It can be seen that the fiber membrane curls up under infrared light irradiation and the temperature gradually increases. The present invention realizes the preparation of a photothermal responsive self-peeling wound dressing.
[0081] Figure 4 This is a comparison diagram of the fiber membranes described in Examples 1, 2, and 3 of the present invention after being co-cultured with bacterial liquid for 24 hours under different near-infrared light irradiation times. Figure 4 In the figure, the Blank group represents pure PVA / PAA fiber membrane, and PAR-1%, PAR-5% and PAR-10% represent AgNR@MSN-CI / PVA / PAA fiber membranes with AgNR@MSN-CI contents of 1%, 5% and 10%, respectively. Figure 4 It can be seen that the antibacterial effect of the fiber membrane can be improved by changing the content of the core-shell structure composite material in the fiber membrane and the number of near-infrared light irradiation. The present invention realizes the preparation of a photothermal responsive antibacterial wound dressing.
[0082] Figure 5 The fiber membrane described in Examples 1, 2, and 3 of the present invention was co-cultured with L929 cells for 12 h ( Figure 5 a) and 24h ( Figure 5 b) The CCK8 test results. Figure 5 It can be seen that as the content of AgNR@MSN increases, the cytotoxicity increases. However, as time goes by, the cells continue to proliferate. The present invention achieves the preparation of highly efficient antibacterial wound dressings within limited cytotoxicity.
[0083] Figure 6 This is the cell morphology after the fiber membrane described in Examples 1, 2, and 3 of the present invention is co-cultured with L929 cells. Figure 6 In the figure, a, b, c, and d represent pure PVA / PAA fiber membranes and AgNR@MSN-CI / PVA / PAA fiber membranes with 1%, 5%, and 10% AgNR@MSN-CI content, respectively. As can be seen from the inset, all cells adhered tightly to the membranes and extended along the direction of a single nanofiber, whether it was pure PVA / PAA nanofiber membranes or PVA / PAA / AgNR@MSN composite nanofiber membranes, indicating that the effect of PVA / PAA / AgNR@MSN composite nanofiber membranes on the viability of individual cells was comparable to that of PVA / PAA fiber membranes.
[0084] In summary, the present invention provides a photothermal responsive composite antibacterial wound dressing and a preparation method and application thereof, wherein the wound dressing comprises a nanofiber membrane that can generate a photothermal response to near-infrared light; the nanofiber membrane is a spinning product obtained by electrostatic spinning using a spinning solution prepared with a biopolymer material and a core-shell structure composite material; the core-shell structure composite material is a composite material with a core-shell structure formed by silver nanorods as a core and mesoporous silica as a shell; wherein the mesoporous silica is doped with an antibacterial drug; the nanosilver antibacterial agent with a core-shell structure provided by the present invention acts as a photosensitizer and an antibacterial agent at the same time; the two antibacterial factors, the antibacterial drug and the nanosilver in the core-shell structure composite material provided by the present invention, synergistically fight bacteria, reduce the amount of nanosilver used, and alleviate the cytotoxicity of nanosilver; the present invention alleviates the problems of nanosilver cytotoxicity and the complicated preparation process and complex ingredients of the self-stripping antibacterial dressing.
[0085] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A photothermal responsive composite antibacterial wound dressing, characterized in that: The wound dressing includes a nanofiber membrane capable of generating a photothermal response to near-infrared light; The nanofiber membrane is a spinning product obtained by electrostatic spinning using a spinning solution prepared with polyvinyl alcohol, polyacrylic acid and a core-shell structure composite material; The core-shell structure composite material is a composite material with a core-shell structure formed by silver nanorods as cores and mesoporous silica as shells; Wherein, the mesoporous silica shell of the core-shell structure composite material is doped with antibacterial drugs.
2. The photothermal responsive composite antibacterial wound dressing according to claim 1, characterized in that: The mass ratio of the polyvinyl alcohol to the polyacrylic acid is 1:1-4, and the core-shell structure composite material accounts for 1%-30% of the mass of the fiber membrane.
3. The photothermal responsive composite antibacterial wound dressing according to claim 1, characterized in that: The molar ratio of the silver nanorods to the mesoporous silica is 1:3-7; the length of the silver nanorods is 60-150 nm, and the aspect ratio is 3-5:1; the thickness of the mesoporous silica shell is 10-80 nm; Wherein, the silver nanorods are wrapped with gold bipyramid seeds.
4. The photothermal responsive composite antibacterial wound dressing according to claim 1, characterized in that: The core-shell structure composite material is prepared according to the following steps: The silver nanorods are dispersed in a chloroform solution, and then added to a CTAB aqueous solution to obtain a homogeneous oil-in-water microemulsion; the chloroform in the obtained microemulsion is evaporated to obtain an AgNR@CTAB solution; The AgNR@CTAB solution and the tetraethyl orthosilicate solution are added into the alkaline aqueous solution containing CTAB. After the reaction is completed, a core-shell structure composite material is obtained. The core-shell structure composite material is soaked in the drug solution for a period of time and then separated to obtain the core-shell structure composite material with the antibacterial drug doped in the mesoporous silica shell.
5. The photothermal responsive composite antibacterial wound dressing according to claim 1, characterized in that: The antibacterial drugs include ciprofloxacin, vancomycin or daqingmycin; The doping amount of the antibacterial drug accounts for 5% to 30% of the mass of the core-shell structure composite material.
6. The photothermal responsive composite antibacterial wound dressing according to claim 1, characterized in that: The core-shell structure composite material can accelerate the release of silver ions and drugs after being irradiated with near-infrared light; the wound dressing can perform photothermal conversion on near-infrared light with a wavelength of 780 to 850 nm.
7. The photothermal responsive composite antibacterial wound dressing according to claim 1, characterized in that: During the electrospinning process, the diameter of the spun nanofibers is 200~1000nm.
8. A method for preparing the photothermal responsive composite antibacterial wound dressing according to any one of claims 1 to 7, characterized in that: include: The polyvinyl alcohol and polyacrylic acid are uniformly mixed in the DCM solution to obtain a transparent solution; After the core-shell structure composite material is uniformly dispersed in the DMF solution, it is added into the transparent solution and stirred for 5 to 8 hours to obtain a spinning solution; The nanofiber membrane is prepared by electrospinning the spinning solution.
9. The method for preparing the photothermal responsive composite antibacterial wound dressing according to claim 8, characterized in that: The electrospinning process parameters were set as follows: voltage 18-20 kV, syringe propulsion speed 0.8-1.2 mL / h, and the distance between the syringe needle and the roller collector was 13-16 cm; The spinning environment temperature was 25±2°C and the relative humidity was 45±2%.
10. Use of the photothermal responsive composite antibacterial wound dressing according to any one of claims 1 to 7 in the preparation of a wound treatment drug.
Citation Information
Patent Citations
Thermo-responsive fibers with photothermal conversion and antibacterial properties and their preparation methods
CN110983483B
Gelatinase responsive photo-thermal oxygen-carrying hydrogel wound dressing and preparation method thereof
CN115920119A
Preparation method of zinc-silver antibacterial material with spherical porous structure
CN118044521A
Cited By
Preparation method and application of hydrophilic breathable gel-based photo-thermal fiber membrane
CN120366964A